"Seeing the error of my ways". Revisiting Paul’s paradigmatic, self-critical remarks in 1 Corinthians 15:8-10 - Joubert, S. (Acta Theologica, 2013)
In the ancient Mediterranean world any public admission of weakness reflected badly on one’s personal status and honour, as well as the public reputation of one’s group. However, in 1 Corinthians 15:8-10 Paul openly admits about being in error in the past regarding the true identity of Christ. Within the larger cultural framework of meaning, the apostle’s graphic confession redefines his prior existence as a form of physical pollution. His open admittance of error also introduces a fresh understanding of God who freely extends grace to the morally impure. Paul serves as the paradigm of the active presence of God’s grace, which ontologically transformed his religious status, as well as his understanding of Christ. In this new relationship, based solely on the grace of God, fitting responses by all grateful recipients entail public confessions of previous error and incessant hard work for the sake of Christ.